PENGARUH DANA ALOKASI UMUM DAN KHUSUS TERHADAP BELANJA DAERAH PADA KABUPATEN/KOTA DI PULAU SUMATERA - William Gani; Septian Bayu Kristanto (Universitas Trunojoyo Madura, 2013)
The purpose of this study is to test the effect of the General Allocation Fund (DAU) and the Special Allocation Fund Expenditure (DAK) that occurs in the district/city on the island of Sumatra, on Government Expenditure. The data was taken from the budget statement and income statement of 2007, which was obtained from 55 districts/cities.The results of the analysis indicate that there was significant effect of the DAU and DAK on government expenditure. The impact of this research was expected to be a smarter government in regulating local spending especially related to APBN and APBD.